A Cree Indian Treatment for Psoriasis: A Longitudinal Study - Morse, Janice M.; Young, David E.; Swartz, Lise; McConnell, Ruth (Culture, 1987)
This article reports on the treatment of 10 non-native patients with psoriasis by a Cree Indian healer. The traditional treatment ceremony is described, and the changes in the course of the disease over a six-month period are documented using the patient’s subjective reports of symptoms, outline tracings of selected lesions, videotapes and photographs. The study is unique in two ways: (1) it included a variety of documentary procedures seldom allowed by native healers and it was conducted under conditions that facilitated evaluation; and (2) to the researchers’ knowledge, it is the first study of traditional native medicine with long-term follow-up of participants. Initially, all patients responded to the treatment, but by the sixth month improvement remained in only six patients. Difficulties encountered when conducting research on traditional healing are discussed and future research directions are indicated.